The Kirati Ritual Language: Evidence from Chhintang and Chhulung - Rai, Ichchha Purna (Gipan, 2017)
This paper deals with the languages used in the rituals practised in Chhintang and Chhulung speech communities. Kirati people have their own culture guided by the mundum. There are four ethnic groups with more than 26 different languages. They have their own separate ritual practices and ritual language. Chhintang and Chhulung have a distinct type of ritual language which is spoken to perform any kind of ritual performances. It has a lot of archaic types of nouns which would be interesting for morpho-semantic analysis. Specially, binomials are unique properties of the ritual language and too complex structurally.